Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus Terhadap Indeks Pembangunan Manusia Dengan Belanja Kesehatan Sebagai Variabel Intervening(Studi Empiris pada Kabupaten/Kota di Jawa Tengah Tahun 2012-2014) - Handayani, Fitri Nur; , Dr. Zulfikar,SE,M.Si (2017)
This study aims to demonstrate empirically the economic growth (PE), revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) that affect the Human Development Index (HDI) with Health Spending as an intervening variable.The population in this study were 35 districts / municipalities located in Central Java province during 2012-2014, with a total sample of 33 District / City contained in the sampling in this research is purposive sampling.T test results showed that the PE and DAU significant effect on the HDI. While the PAD and DAK no direct impact on the HDI. PE and DAU directly affect the HDI through BKsht, while the PAD and DAK no direct impact on the HDI through BKsht. In the path analysis showed that determine the effect of PE and PAD to IPM been a direct path without passing through BKsht, while DAU and DAK to IPM been pathway indirectly through BKsht